Pentingnya Perbandingan Nilai-Nilai Spesifik antara Mahasiswa Akuntansi dan Teknik Sipil - Sri Suryaningsum; Sucahyo Heriningsih; Ketut Aryani (Journal of Accounting and Investment, 2005)
This research analyzed, appeals and differentiaves the specific values between accounting students and civil engineering students from some universities in Jogjakarta. Specific values is value which differentiaves student behavior specifically where specific values contens about individuality value, social value, theoretical values, and esthetic value. The data is used a questioner from Rokeach’s model and Schwartz’s model. Measurement is conducted with Likert Scale. The analysis instrument uses t-test. The result of analysis show that there differentiation the specific value between accounting students and engineering students where the differentiation is in the esthetic value.